Collaborative design process and product knowledge methodology for mechatronic systems - Mcharek, Mehdi; Hammadi, Moncef; Azib, Toufik; Larouci, Cherif; Choley, Jean-Yves (Computers in industry, 2019)
•This paper presents a new methodology for collaborative design and reuse for mechatronic systems.•The methodology is based on Knowledge Management to assist users in the different steps of the design cycle.•We present the product and process design knowledge structure to allow the exchange between system and disciplinary levels.•A UML model and the associated methodology are detailed in accordance with the design cycle steps.•A demonstrator is implemented and applied successfully to an industrial scenario about the Electronic Throttle Body system. Recent advances in design techniques promote the development of concurrent engineering to reduce the time and cost of the design cycle. This is particularly necessary for mechatronic design which involves several disciplines. But companies have to address challenges associated with collaboration and reuse. The mechatronic design evolves from the system level to the multiple-disciplinary level. This requires that system engineers and disciplinary engineers collaborate closely for an integrated and continuous product development process. However, the heterogeneity of tools used in system level and disciplinary level with the lack of a common knowledge basis creates a gap between them. Thus, the focus of this paper is to develop a knowledge management framework suitable for mechatronic concurrent design and capable to harmonize the overall design cycle. Our contribution lies in structuring knowledge at the system and disciplinary levels to ensure the traceability between them. Our methodology called Collaborative Design Process and Product Knowledge (CDPPK) is detailed with the associated meta-model. A demonstrator is also presented and applied successfully to a collaborative industrial scenario concerning the Electronic Throttle Body (ETB).